An integrated map to developing the innovation and commercialization potential of Iranian knowledge-based companies - Amir Ehsan Zahedi; Seyyed Habibollah Mirghfoori; Ali Morovati Sharif Abadi (Cogent Business & Management, 2018)
Innovation means the economic or social impact of the object on the market. Many inventions are being made and innumerable ideas are created; but among them, only a small number can affect the market, considered as new ideas and inventions. The rest of them disappear in various stages of their evolution, from the stage of idea to the market stage. Establishing knowledge-based companies in science and technology parks in order to commercialize ideas is one of the first serious work that has been done in the country to transform innovation into technology. The existence of an effective system for innovation and commercialization with respect to various types of specific resources required by the company to achieve sustainable competitive advantage is considered as a strategic choice. The purpose of this study is to develop an integrated map to developing the innovation and commercialization potential of knowledge-based companies in Iran. This study has been conducted using Strategic Options Development and Analysis (SODA) approach. The population consisted of experts in the field of knowledge-based companies. Using a theoretical sampling, 13 managers of knowledge-based companies in Tehran province were selected as participants in the research. Data were collected through semi-structured interview with general guidance. The final map drew and analyzed using Decision Explorer (DE) software. Accordingly, Human resources—Technology—Culture—Political factors—Financial and capital resources—Physical and structural resources, are key options in development of the innovation and commercialization potential of knowledge-based companies. By focusing on these options, the strategies have been developed for each of them to reinforce the key issues and to achieve the goals at the higher level.
Keywords: 650